2021
DOI: 10.1111/pbr.12965
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating natural variation, heritability, and genetic advance of photosynthetic traits in rice (Oryza sativa)

Abstract: Despite significant advances to harvest index and interception efficiency, photosynthesis has remained largely unimproved through conventional breeding approaches. However, increasing photosynthetic efficiency is a key method for enhancing crop productivity, yield, and sustainability. In this study, photosynthetic and morphological traits were characterized in indica rice to examine natural variation and the potential for hybridization in the future. Additionally, broad‐sense heritability (H2) was calculated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 58 publications
1
20
0
Order By: Relevance
“…These findings suggest that TPU limitation to leaf photosynthesis may be regulated by sink feedback at the whole-plant scale. Acevedo-Siaca et al (2021) showed that like V cmax and J max , T p estimated for 30 rice accessions had high heritability. Data of Acevedo-Siaca et al (2021) further showed that rice A max at CO 2 saturation was highly heritable but A max at ambient [CO 2 ] was not, suggesting that genotypic variation in A max might be caused by genotypic sink limitation ( Fabre and Dingkuhn, 2022 ).…”
Section: Natural Variation Of Photosynthetic Parametersmentioning
confidence: 94%
See 2 more Smart Citations
“…These findings suggest that TPU limitation to leaf photosynthesis may be regulated by sink feedback at the whole-plant scale. Acevedo-Siaca et al (2021) showed that like V cmax and J max , T p estimated for 30 rice accessions had high heritability. Data of Acevedo-Siaca et al (2021) further showed that rice A max at CO 2 saturation was highly heritable but A max at ambient [CO 2 ] was not, suggesting that genotypic variation in A max might be caused by genotypic sink limitation ( Fabre and Dingkuhn, 2022 ).…”
Section: Natural Variation Of Photosynthetic Parametersmentioning
confidence: 94%
“…Where CO 2 or light response curves are measured that allow the estimation of V cmax and J max , the variation of A max is often associated with V cmax or J max , or both ( Driever et al , 2014 ; Jahan et al , 2014 ; Carmo-Silva et al , 2017 ; Silva-Perez et al, 2020 ; Acevedo-Siaca et al , 2021 ). In general, V cmax and J max estimated across genotypes/accessions are highly correlated ( Driever et al , 2014 ; McAusland et al , 2020 ; Mathan et al , 2021 ).…”
Section: Natural Variation Of Photosynthetic Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the above, it is possible that the greater heritability of A max compared with A sat (Acevedo‐Siaca et al, 2021) in part reflects genotypic variation in source–sink relations. This effect is amplified when high or saturating CO 2 levels are applied.…”
Section: Why Is Heritability Of Amax Greater Than That Of Asat?mentioning
confidence: 99%
“…As an alternative hypothesis explaining the superior heritability of A max compared with A sat (Acevedo‐Siaca et al, 2021), genotypic variation in A sat (ambient [CO 2 ]) may have been simply overwhelmed by noise in stomatal conductance, possibly amplified by plant exposure to the (assumedly) low radiation levels caused by the wet season conditions and additional shading by the screenhouse structure. The CO 2 ‐saturation implemented to measure A max would have eliminated this noise, resulting in greater H 2 for A max .…”
Section: Why Is Heritability Of Amax Greater Than That Of Asat?mentioning
confidence: 99%